Perinatal Characteristics and Outcome of Neonates at NICU of a Tertiary Level Hospital in Bangladesh - Shahidullah, Mohammod; Hasan, M Zahidul; Jahan, Ismat; Ahmed, Firoz; Dey, Arjun Chandra; Dey, Sanjoy Kumer; Mannan, MA (Bangladesh Journal of Child Health, 2017)
Background: One of the Millennium Development Goals (MDG-4) is to reduce child mortality up to two-thirds by 2015. In most developing countries, a higher proportion of neonatal deaths are observed. It has been recognized that without a substantial reduction in neonatal deaths, MDG-4 will not be met. Objective: To assess the perinatal characteristics, pattern of admissions and outcome of neonates in a tertiary care centre in Bangladesh. Methods: A retrospective review of consecutive neonatal admissions to Bangabandhu Sheikh Mujib Medical University, between January and December 2013, was conducted. Data were collected from the neonatal admission, discharge and death registers. Standard definitions of the conditions were used to diagnose the clinical conditions. Results: Total 683 neonates were admitted to the NICU. Among them 56.1% were inborn and males were 56.8%. Total 61.3% neonates were low birth weight and 60.3 % were preterm. The overall cesarean section rate was 61.9%. Total 35.3% neonates had sepsis and perinatal asphyxia was present in 16.8% neonates. Congenital anomaly was present in 17.6% neonates. The mean duration of hospital stay was 11.1 days and overall mortality rate was 14.9%. Conclusion: Prematurity, neonatal infections, birth asphyxia and congenital anomalies were the main causes of neonatal hospital admission and neonatal deaths in this study. Bangladesh J Child Health 2017; VOL 41 (1) :34-39